Expression profiling reveals altered satellite cell numbers and glycolytic enzyme transcription in nemaline myopathy muscle - Sanoudou, D.; Haslett, J. N.; Kho, A. T.; Guo, S.; Gazda, H. T.; Greenberg, S. A.; Lidov, H. G.; Kohane, I. S.; Kunkel, L. M.; Beggs, A. H. (Proc Natl Acad Sci U S AProc Natl Acad Sci U S AProc Natl Acad Sci U S A, 2003)
The nemaline myopathies (NMs) are a clinically and genetically heterogeneous group of disorders characterized by nemaline rods and skeletal muscle weakness. Mutations in five sarcomeric thin filament genes have been identified. However, the molecular consequences of these mutations are unknown. Using Affymetrix oligonucleotide microarrays, we have analyzed the expression patterns of >21,000 genes and expressed sequence tags in skeletal muscles of 12 NM patients and 21 controls. Multiple complementary approaches were used for data analysis, including geometric fold analysis, two-tailed unequal variance t test, hierarchical clustering, relevance network, and nearest-neighbor analysis. We report the identification of high satellite cell populations in NM and the significant down-regulation of transcripts for key enzymes of glucose and glycogen metabolism as well as a possible regulator of fatty acid metabolism, UCP3. Interestingly, transcript level changes of multiple genes suggest possible changes in Ca(2+) homeostasis. The increased expression of multiple structural proteins was consistent with increased fibrosis. This comprehensive study of downstream molecular consequences of NM gene mutations provides insights in the cellular events leading to the NM phenotype.
Keywords: Adult; Calcium Signaling; Case-Control Studies; Cell Count; Cell Cycle; Energy Metabolism; Expressed Sequence Tags; gene expression profiling; Glycolysis/*genetics; Humans; Infant, Newborn; Models, Biological; Muscle, Skeletal/metabolism/pathology; Myopathies, Nemaline/*genetics/metabolism/*pathology; Oligonucleotide Array Sequence Analysis; Phenotype